2020
DOI: 10.1186/s13046-020-01677-w
|View full text |Cite
|
Sign up to set email alerts
|

FadA promotes DNA damage and progression of Fusobacterium nucleatum-induced colorectal cancer through up-regulation of chk2

Abstract: Background Globally, colorectal cancer (CRC) affects more than 1 million people each year. In addition to non-modifiable and other environmental risk factors, Fusobacterium nucleatum infection has been linked to CRC recently. In this study, we explored mechanisms underlying the role of Fusobacterium nucleatum infection in the progression of CRC in a mouse model. Methods C57BL/6 J-Adenomatous polyposis coli (APC) Min/J mice [APC (Min/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 57 publications
(64 reference statements)
2
71
0
Order By: Relevance
“…This is proposed to be due to the expression of proteins that have antiapoptotic, growth factor or cytokine that enhance cancer cell growth, metastasis or resistance to therapy [ 17 ]. However, F. nucleatum has been shown to also express high levels of virulence factors such as FadA , Fap2 and MORN2 proteins [ 19 ]. Studies have demonstrated that the dominant microbiome is very similar in primary and metastatic tumors [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is proposed to be due to the expression of proteins that have antiapoptotic, growth factor or cytokine that enhance cancer cell growth, metastasis or resistance to therapy [ 17 ]. However, F. nucleatum has been shown to also express high levels of virulence factors such as FadA , Fap2 and MORN2 proteins [ 19 ]. Studies have demonstrated that the dominant microbiome is very similar in primary and metastatic tumors [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further F. nucleatum elicits substantially greater amounts of pro-inflammatory TNF-α gene expression, which can lead to increased IDO1 activation [ 99 , 106 , 114 , 115 ]. Both F. Nucleatum and Peptostreptococcus anaerobius can attach to the cancer cells through cell surface attachment proteins, activating the PI3k-Akt pathway leading to cell proliferation [ 116 , 117 ]. Intriugingly, both of the species can also produce high levels of indoles from Trp metabolism.…”
Section: Alterations In Microbial Trp Metabolism In Colon Carcinogenesismentioning
confidence: 99%
“…However, E. coli is far from the only species with this capability. Molecular studies of F. nucleatum have discovered the virulence protein FadA and its involvement in the transformation of epithelial cells and the promotion of colon tumorigenesis [ 63 ]. A meta-analysis of CRC fecal metagenomes confirmed the significant enrichment in both the colibactin-producing gene cluster pks and the F. nucleatum adhesin fadA [ 53 ].…”
Section: Crc and Gut Microbiotamentioning
confidence: 99%